Basal Rot of Narcissus: Understanding Pathogenicity in Fusarium oxysporum f. sp. narcissi - Taylor, Andrew; Armitage, Andrew D.; Handy, Claire; Jackson, Alison C.; Hulin, Michelle T.; Harrison, Richard J.; Clarkson, John P. (Frontiers in Microbiology, 2019)
Fusarium oxysporum is a globally distributed soilborne fungal pathogen causing root rots, bulb rots, crown rots and vascular wilts on a range of horticultural plants. Pathogenic F. oxysporum isolates are highly host specific and are classified as formae speciales. Narcissus is an important ornamental crop and both the quality and yield of flowers and bulbs can be severely affected by a basal rot caused by F. oxysporum f. sp. narcissi (FON). 154 Fusarium isolates were obtained from different locations and Narcissus cultivars in the UK, representing a valuable resource. A subset of 30 F. oxysporum isolates were all found to be pathogenic and were therefore identified as FON. Molecular characterisation of isolates through sequencing of three housekeeping genes, suggested a monophyletic origin with little divergence. PCR detection of 14 Secreted in Xylem (SIX) genes, previously shown to be associated with pathogenicity in other F. oxysporum f.spp., revealed different complements of SIX7, SIX9, SIX10, SIX12 and SIX13 within FON isolates which may suggest a race structure. SIX gene sequences were unique to FON and SIX10 was present in all isolates, allowing for molecular identification of FON for the first time. The genome of a highly pathogenic isolate was sequenced and lineage specific regions identified which harboured putative effectors including the SIX genes. Real-time RT-PCR, showed that SIX genes and selected putative effectors were expressed in planta with many significantly upregulated during infection. This is the first study to characterise molecular variation in FON and provide an analysis of the FON genome. Identification of expressed genes potentially associated with virulence provides the basis for future functional studies and new targets for molecular diagnostics.